PENGARUH PBL TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DI ERA KURIKULUM MERDEKA - Sape, Herwandi; Masril Aguswandi Tudjuka (Jurnal Penalaran dan Riset Matematika, 2025)
This study aims to analyze the effect of the Problem Based Learning (PBL) model on high school students' mathematical problem-solving abilities within the context of the Merdeka Curriculum implementation. The research employed a quantitative approach using a quasi-experimental method with a Non-Equivalent Control Group Design. The subjects were two eleventh-grade classes at SMA Negeri 3 Maros, assigned as the experimental and control groups, selected through purposive sampling. The instrument used was a written pre-test and post-test based on problem-solving indicators developed by George Polya. Data were analyzed using both descriptive and inferential statistics, including normality testing (Shapiro-Wilk), homogeneity of variance testing (Levene’s Test), independent sample t-test, paired sample t-test, and gain score calculation using Hake’s normalized gain formula. The results indicated a significant difference between the experimental and control groups, with a greater improvement in problem-solving ability observed in the experimental group. The PBL model was proven effective in fostering active engagement, critical thinking, and students’ analytical skills in solving mathematical problems. This research recommends the implementation of the PBL model as a relevant and adaptive instructional strategy to strengthen the Merdeka Curriculum, particularly in high school mathematics education